A p-tert-Butyldihomooxacalix[4]arene Based Soft Gel for Sustained Drug Release in Water - Guo, Hao; Zhang, Runmiao; Han, Ying; Wang, Jin; Yan, Chaoguo (Frontiers in Chemistry, 2020)
P-tert-butyldihomooxacalix[4]arene is a well-known calix[4]arene analog in which one CH2 bridge is replaced by one -CH2OCH2- group. Thus, dihomooxacalix[4]arene has a slightly larger cavity than that of calix[4]arene and usually possesses a more flexible cone conformation, and the bridged oxygen atom might provide additional binding sites. Here, we synthesized a new functional p-tert-butyldihomooxacalix[4]arene 1 through Ugi reaction with good yield (70%), starting from condensed p-tert-butyldihomooxacalix[4]arene O-alkoxy–substituted benzaldehydes, benzoic acid, benzylamine, and cyclohexyl isocyanide. Proton nuclear magnetic resonance spectroscopy (1H NMR), 13C NMR, IR, and diffusion-ordered 1H NMR spectroscopy (DOSY) methods were used to characterize the structure of 1. Then soft gel was prepared by adding 1 into cyclohexane directly. It shows remarkable thermoreversibility and can be demonstrated for several cycles. As is revealed by scanning electron microscopy (SEM) images, xerogel showed highly interconnected and homogeneous porous network structures, and hence, the gel is suitable for storage and controlled release.